2021
DOI: 10.1101/2021.08.06.454924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heavy isotope labeling and mass spectrometry reveal unexpected remodeling of bacterial cell wall expansion in response to drugs

Abstract: Antibiotics of the β-lactam (penicillin) family inactivate target enzymes called D,D-transpeptidases or penicillin-binding proteins (PBPs) that catalyze the last cross-linking step of peptidoglycan synthesis. The resulting net-like macromolecule is the essential component of bacterial cell walls that sustains the osmotic pressure of the cytoplasm. In Escherichia coli, bypass of PBPs by the YcbB L,D-transpeptidase leads to resistance to these drugs. We developed a new method based on heavy isotope labeling and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…PG recycling is stimulated in the +CRO condition 49 . This implies that the rescue of PBPs by YcbB reduces but does not abolish the high anabolic demand necessary to feed the PG assembly pathway in the presence of the drug.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PG recycling is stimulated in the +CRO condition 49 . This implies that the rescue of PBPs by YcbB reduces but does not abolish the high anabolic demand necessary to feed the PG assembly pathway in the presence of the drug.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the inactivation of SltY favors YcbB-mediated resistance to β-lactams, with uncross-linked glycan strands formed by the elongasome complex serving as suitable substrates for the assembly of a functional PG polymer 7 . Pulse-labeling experiments indicated that YcbB supported PG polymerization via a two-step mechanism involving (i) assembly of 3 → 3 cross-linked glycan strands followed by (ii) insertion of the resulting neo-synthesized polymer into the existing PG 49 . In the present work, we provide direct evidence that this mode of peptidoglycan polymerization requires a functional elongasome, supporting glycan strand polymerization by catalytically active RodA (Fig.…”
Section: Discussionmentioning
confidence: 99%